Morphine-Induced Elevation of Reactive Oxygen Species Attenuates Chemotherapy Efficacy in Diverse Cancer Cell Types - Chen, Gong; Zeng, Si; Wang, Bin; Wang, Daguo; Ding, Jie; Feng, Tao (Current Molecular Medicine, 2025)
BackgroundMorphine, a mu-opioid receptor (MOR) agonist commonly utilized in clinical settings alongside chemotherapy to manage chronic pain in cancer patients, has exhibited contradictory effects on cancer, displaying specificity toward certain cancer types and doses.ObjectiveThe aim of this study was to conduct a systematic assessment and comparison of the impacts of morphine on three distinct cancer models in a preclinical setting.MethodsViability and apoptosis assays were conducted on a panel of cancer cell lines following treatment with morphine, chemotherapy drugs alone, or their combination. Oxidative stress levels, along with the activities of superoxide dismutase and catalase, were measured. Rescue studies were also carried out using antioxidant reagents.ResultsMorphine induces resistance to conventional chemotherapeutic agents. It was observed that while morphine affected cell viability differently among ovarian cancer, anaplastic thyroid cancer, and oral squamous cell carcinoma, at concentrations that did not directly impact cancer cell viability, it significantly mitigated the inhibitory effects of chemotherapeutic agents across all tested cancer cells. This phenomenon persisted irrespective of the chemotherapeutic agent used, including cisplatin, doxorubicin, and 5-FU. It remained unaffected by adding naloxone, the MOR receptor antagonist, indicating that morphine's mechanism is independent of the μ-opioid receptor. Moreover, it was demonstrated that morphine heightened cellular reactive oxygen species (ROS) levels and suppressed the activities of superoxide dismutase and catalase. Rescue studies revealed that the addition of antioxidant reversed the protective impact of morphine on cancer cells against chemotherapy.ConclusionThese findings hold promise in potentially guiding the clinical application of morphine for cancer patients undergoing chemotherapy.
Keywords: oxidative stress